Appearance of SERS activity in single silver nanoparticles by laser-induced reshaping. Issue 1 (11th December 2018) - Chaudhari, Kamalesh; Ahuja, Tripti; Murugesan, Vasanthanarayan; Subramanian, Vidhya; Ganayee, Mohd Azhardin; Thundat, Thomas; Pradeep, Thalappil
Abstract : This study demonstrates that single silver nanoparticles which are not initially SERS active become SERS active by laser-induced reshaping/reorientation. Abstract : We report simultaneous plasmonic scattering and Raman spectroscopic observations of single citrate capped silver nanoparticles (AgNPs) which exhibit surface enhanced Raman scattering (SERS) upon meeting specific conditions induced by laser (532 nm) exposure. We show that nanoparticles which are not initially SERS active become SERS active by laser-induced reshaping/reorientation. A set-up developed for these observations enabled in situ high speed time-lapse characterization using plasmonic and Raman spectroscopies in conjunction with dark-field microscopy (DFM). Changes in the AgNPs were confirmed by monitoring plasmonic scattering spectra and DFM images. Time-lapse observations have shown that laser-induced changes in the plasmonic properties of AgNPs resulted in the appearance of SERS. Spectral matching between plasmon resonance and downward molecular vibronic transitions for molecules adsorbed on the surface of plasmonic nanomaterials is attributed to the nanoparticle SERS. We have further shown that the release of silver ions by silver nanoparticles can be the probable reason for their plasmonic changes. Gold nanoparticles inert to such mild (850 μW, 532 nm) laser-induced changes do not exhibit the appearance of SERS.